Surgical correction of pterygium colli - Reichenberger, Matthias; Goertz, Ole; Lehnhardt, Markus; Germann, Günter; Ryssel, Henning; Czermak, Christoph; Kolbenschlag, Jonas (Journal of pediatric surgery, 2013)
Background/Purpose - Webbing of the neck is a deformity seen in various syndromes, including Turner's, Klippel-Feil, or Escobar-Syndrome. There is little information in literature to provide the surgeon with treatment options for these children. We reviewed our experience with the surgical correction of pterygium colli deformity in eleven patients. - Methods - A retrospective review was conducted on all patients that underwent surgical correction of pterygium colli deformity within the last 8 years. Data recorded included patient demographics, diagnostic evaluation, surgical treatment, complications, and outcome. - Results - Eleven patients underwent an operation to correct pterygium colli deformity. Six patients had z-plasties, and three patients underwent bilateral excision of an ellipsoid portion of skin and closure via unilateral advancement flaps. We later modified our technique to combine the unilateral advancement flap with Z-Plasties. The mean age at operation was 10.7 years (range 2-23 years). No postoperative wound infections occurred. Mild recurrence of webbing was found in one case. In four patients we found mild to moderate hypertrophic scarring. Average overall content was 7.8 (scale of 0-10, 10 being total content), and all patients, respectively their parents, would undergo the surgery again. Mean length of follow-up was 28.3 months. - Conclusion - Our study shows that overall patient satisfaction is very high, but an accurate preoperative planning with the patient and parents and an honest discussion of all questions and concerns raised by the parents are essential.
Gesehen am 20.12.2021